Research on transient energy suppression strategy of intrinsically safe output power supply for mine - Changna GUO (Meikuang Anquan)
In response to the requirements of GB/T 3836.4—2021 Explosive atmosphere Part 4: Equipment with protection by intrinsic safety “i” for outputting transient energy of intrinsically safe power sources based on the principle of semiconductor rapid short circuit protection, taking typical mining “ib” class explosion-proof and intrinsically safe power supplies and intrinsically safe battery power supplies as research objects, the study clarifies the transient energy testing device and transient energy calculation method. According to the experimental verification and comparison, the reasons for the failure of the transient energy experiment of the output intrinsically safe power supply are analyzed, and it is verified that the protection time, the reaction speed of semiconductor chip, the short-circuit instantaneous voltage and current value in the over-voltage and over-current protection circuit are the key parameters affecting the transient energy; based on the actual design, the protection process is analyzed, the method of reducing transient energy by TVS tube is excluded, and the influence of inductor on transient energy before and after the power supply overvoltage and over-current protection circuit is studied, which provides a reference for the design of the output intrinsically safe power supply for mining.